Ionic liquid containing high-density polyethylene supported tungstate: a novel, efficient, and highly recoverable catalyst - Mousavi, Farideh; Elhamifar, Dawood; Kargar, Shiva; Elhamifar, Davar (Frontiers in Chemistry, 2024)
In the present work, a novel nanocomposite material involving ionic liquid and high-density polyethylene supported tungstate (PE/IL-WO4=) is synthesized, characterized and its catalytic application is investigated. The coacervation method was used to incorporate 1-methyl-3-octylimidazolium bromide ([MOIm][Br]) ionic liquid in high-density polyethylene, resulting in a PE/IL composite. Subsequently, tungstate was anchored on PE/IL to give PE/IL-WO4= catalyst. The PXRD, FT-IR, EDX, TGA, and SEM analyses were used to characterize the PE/IL-WO4= composite. This material demonstrated high catalytic efficiency in the synthesis of bioactive tetrahydrobenzo[a]xanthen-11-ones under green conditions. The recoverability and leching tests were performed to investigate the stability and durability of the designed PE/IL-WO4= catalyst under applied conditions.